Precipitous Increase of Bacterial CRISPR-Cas Abundance at Around 45°C - Lan, Xin-Ran; Liu, Zhi-Ling; Niu, Deng-Ke (Frontiers in Microbiology, 2022)
Although performing adaptive immunity, CRISPR-Cas systems are present in only 40% of bacterial genomes. We observed an abrupt increase of bacterial CRISPR-Cas abundance at around 45degreeC. Phylogenetic comparative analyses confirmed that the abundance correlates with growth temperature only at the temperature range around 45degreeC. From the literature, we noticed that the diversities of cellular predators (like protozoa, nematodes, and myxobacteria) have a steep decline at this temperature range. The grazing risk faced by bacteria reduces substantially at around 45degreeC and almost disappears above 60degreeC. We propose that viral lysis would become the dominating factor of bacterial mortality, and antivirus immunity has a higher priority at higher temperatures. In temperature ranges where the abundance of cellular predators does not change with temperature, the growth temperatures of bacteria would not significantly affect their CRISPR-Cas contents. The hypothesis predicts that bacteria should also be rich in CRISPR-Cas systems if they live in other extreme conditions inaccessible to grazing predators.